Teaching Children’s Motor Skills for Team Games Through Guided Discovery: How Constraints Enhance Learning - Newell, Karl M.; Rovegno, Inez (Frontiers in Psychology, 2021)
In this paper we examine the role of instructional strategies as constraints within a discovery learning framework for the teaching of open skill team ball games to elementary school-aged children. The cohesive and adaptive integration of constraints (individual, environment, and task) by practitioners of movement and physical activity (instructor, teacher, coach) is proposed as the pathway to exploiting the effectiveness of guided discovery learning. The qualitative analysis of the practical instantiations of this framework by expert teachers is examined with respect to the learning of open skill team invasion games (e.g., basketball, soccer). The primary constraints to action in this learning-teaching developmental framework are coordinated so as to keep the self-organization of skill development (movement pattern and tactics) continually evolving, while preserving the child’s motivation and enjoyment for the expanding repertoire and performance capacity of his/her perceptual-motor skills. In this open skill and elementary school age-related context, generality and specificity are both necessary and complementary in the expression of task, skill and practice influences on motor learning and performance.